Evaluation of the motion of lung tumors during stereotactic body radiation therapy (SBRT) with four-dimensional computed tomography (4DCT) using real-time tumor-tracking radiotherapy system (RTRT). Issue 2 (February 2016) - Harada, Keiichi; Katoh, Norio; Suzuki, Ryusuke; Ito, Yoichi M.; Shimizu, Shinichi; Onimaru, Rikiya; Inoue, Tetsuya; Miyamoto, Naoki; Shirato, Hiroki
Highlights: 4DCT MIP is useful to establish the mean amplitude of tumor movement during SBRT. 4DCT MIP underestimates the maximum amplitude during SBRT. Caution must be paid to determine the margin with 4DCT especially for lower lobe. Abstract: Purpose: We investigated the usefulness of four-dimensional computed tomography (4DCT) performed before stereotactic body radiation therapy (SBRT) in determining the internal margins for peripheral lung tumors. Methods and Materials: The amplitude of the movement of a fiducial marker near a lung tumor measured using the maximum intensity projection (MIP) method in 4DCT imaging was acquired before the SBRT (AmpCT ) and compared with the mean amplitude of the marker movement during SBRT (Ampmean ) and with the maximum amplitude of the marker movement during SBRT (Ampmax ) using a real-time tumor-tracking radiotherapy (RTRT) system with 22 patients. Results: There were no significant differences between the means of the Ampmean and the means of the AmpCT in all directions (LR, P = 0.45; CC, P = 0.80; AP, P = 0.65). The means of the Ampmax were significantly larger than the means of the AmpCT in all directions (LR, P < 0.01; CC, P = 0.03; AP, P < 0.01). In the lower lobe, the mean difference of the AmpCT from the mean of the Ampmax was 5.7 ± 8.0 mm, 12.5 ± 16.7 mm, and 6.8 ± 8.5 mm in the LR, CC, and AP directions, respectively. Conclusions: Acquiring 4DCT MIP images before the SBRT treatment is useful to establish the mean amplitude for a patient during SBRT but it underestimates the maximum amplitude during actual SBRT. Caution must be paid to determine the margin with the 4DCT especially for tumors at the lower lobe where it is of the potentially greatest benefit.